Rancang Bangun Mini Rov dengan Penggunaan PWM Speed Controller Module sebagai Sistem Kendali: Design and Build Mini Rov Using PWM Speed Controller Module as A Control System - Baswantara, Arif; Alfaris, Lulut; Firdaus, Anas Noor; Bramawanto, Rikha; Hareva, Batih Shendy Capri; Putri, Miranda (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2023)
Remotely Operated Vehicle (ROV) is an underwater vehicle or robot designed to able to move in the water. The increasing need for ROV in the future will require an ROV that is easy to build and operate. This study aims to design and build an ROV that is easy to manufacturing and easy to operate, which can be used for observation purposes in the future. The ROV designed with dimensions of length was 311,89 mm, width was 240 mm and height was 180 mm. ROV had three thruster motors with Pulse Width Modulation (PWM) Speed Controller Module as a control system. The ROV test were conducted motion tests and maneuvering tests, with the results shown that the ROV had an average forward speed of 0,26 m/s with the turning time was 6,3 s for 180° to portside, 6,7 s for 180° to starboard and time for circular motion was 8,2 s. The ROV’s motion test and maneuvering test showed good results, so that further development plans for this ROV can be carried out.